(untitled) (Journal of Hama University, 2020)
This research aims to know the better technique (total etch and self etch) that achieve the higher compressive resistance for teeth restored with resin reinforced fiber glass posts affixed using those techniques through a comparative study between these two techniques and using the test of compressive resistance and study the pattern of failure happening. Sample of this research consisted of 40 lower premolars their crowns cutted horizontally 2 mm away from the cementoenamel junction and root canal endodontically treated with suitable instruments and divided into 2 groups according to the adhesive cement used to lute of the glass fiber posts which used to restore the teeth: Group A: posts luted with resin cement based on total etch technique. Group B: posts luted with adhesive resin cement based on self etch technique Then, cores built up of all the teeth of composite and then, teeth crowned with metal crowns cemented with zinc phosphate cement. Each specimen was secured in a universal load-testing machine. A compressive load was applied at 45º degree angle at a crosshead speed of 1 mm/min to the long axis of the tooth until fracture occurred. Compression resistance recorded for each sample, and the statistical study was conducted for the results of the tests. The results of mechanical test indicated that there is no statistically significant differences in the average compressive resistance between two groups.Also that there is no statistically significant differences in the frequencies place of failure between two groups. Compressive resistance of treated teeth restored with glass fiber posts doesn’t affect when attached to two different adhesive techniques (Total etch and Self etch) using resin cement and adhesive resin cements. The pattern of failure in all samples is the preferred type and capable to restore and repair.